Distribusi mikroplastik pada sedimen di Muara Badak, Kabupaten Kutai Kartanegara - Intan Sari Dewi; Anugrah Aditya Budiarsa; Irwan Ramadhan Ritonga (Depik, 2015)
Abstract. The distribution of microplastic was studied in the Muara Badak districts Kutai Kartanegara regency in May 2015. Sediment samples were taken from four stations that represent residential, in mangrove, near the beach and away from residential areas. Sediment samples were taken using the pipe at a depth of 0-10 cm - 10-20 cm, then the observed and calculated abundance of microplastic. The results showed that the type microplastic found is a fragment, film and fiber. At Station 1 found fragments about 100.2-201.3 particle/kg, the film about 69.6-79.9 particles/kg and fiber  about 43.1-50.9 particles/kg, the stations 2 found of fragments about 146.5-238.8 particle/kg, the film about 53.2-81.9 particles/kg and fiber about 48.8-75.5 particles/kg, stations 3 found of fragments about 204.2-207.9 particles/kg, the film about 107.7-126.5 particle/kg and fiber about 26.1-39.9 particles/kg, station 4 found of fragments about 167.6-220 particle/kg, the film about 59.7-69.5 particle/ kg and fiber about 47.5-55.3 particles/kg. Keywords: Depth; Microplastic; Muara Badak; Sediment  Abstrak. Distribusi mikroplastik diteliti di Kecamatan Muara Badak Kabupaten Kutai Kartanegara pada bulan Mei 2015. Sampel sedimen diambil dari 4 stasiun yang mewakili pemukiman penduduk, dekat sungai, dekat pantai dan jauh dari pemukiman penduduk. Sampel sedimen diambil menggunakan pipa paralon pada kedalaman 0-10 cm – 10-20 cm, kemudian diamati dan dihitung kelimpahan mikroplastik. Hasil penelitian menunjukan bahwa jenis mikroplastik yang ditemukan adalah fragmen, film dan fiber. Pada stasiun 1 ditemukan fragmen berkisar 100,2-201,3 partikel/kg, film berkisar 69,6-79,9 partikel/kg dan fiber berkisar 43,1-50,9 partikel/kg, stasiun 2 ditemukan fragmen berkisar 146,5-238,8 partikel/kg, film berkisar 53,2-81,9 partikel/kg dan fiber berkisar 48,8-75,2 partikel/kg, stasiun 3 ditemukan fragmen berkisar 204,2-207,9 partikel/kg, film berkisar 107,7-126,5 partikel/kg dan fiber berkisar 26,1-39,9 partikel/kg, stasiun 4 ditemukan fragmen berkisar 167,6-220 partikel/kg, film berkisar  59,7-69,5partikel/kg dan fiber berkisar 47,5-55,3 partikel/kg.Kata kunci:  Kedalaman; Mikroplastik; Muara Badak; Sedimen